Investigation of Adsorption of 5-Fluorouracil and 5-Bromouracil onto Sepiolite and Loughlinite: An IR Spectroscopic Study - Akalın, Elif; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Asian Journal Of Chemistry, 11/100 Rajendra Nagar, Sector 3,, Sahibabad 201 005, Ghaziabad, India, 2014)
The adsorption of 5-fluorouracil (5FU) and 5-bromouracil (5BrU) by sepiolite and loughlinite (natural Na-sepiolite) has been investigated using FT-IR spectrometry. The spectroscopic results indicate that 5-halogenouracils adsorbed on sepiolite and loughlinite are coordinated to surface hydroxyls and/or to Lewis acidic centers by hydrogen bonding interaction through the oxygen lone pairs. Some intensity and frequency changes in the OH stretching and deformation bands of surface hydroxyls (Si-OH) of the 5-fluorouracil and 5-bromouracil treated sepiolite and loughlinite were observed. Adsorption capacity of the sepiolite is found to be higher than loughlinite for 5-halogenuracils. Moreover adsorption capacity of clays were found to decrease in the order 5-fluorouracil >5-bromouracil.
Keywords: Adsorption; 5-Bromouracil; Clays; 5-Fluorouracil; IR spectroscopy; Loughlinite; Sepiolite; Vibrational-Spectra; Montmorillonite; Uracil; 5-Chlorouracil; Tautomerism; Derivatives; Acid